Qué tan sensibles son los mercados financieros al brote por COVID-19? Evidencia de los mercados de Estados Unidos y Colombia; How sensitive are financial markets to COVID-19 outbreak? Evidence from the United States and Colombia markets - James Duvan Ramírez Quintero; Jefferson Marulanda Piedrahita; José Rafael Tovar Cuevas; Diego Fernando Manotas-Duque (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2023)
– In this article, the market risk associated with the financial markets of New York and Colombia is evaluated in three periods belonging to the 2019-2020-time window, characterized by shocking economic and social conditions such as the oil price war between Saudi Arabia and Russia and the global pandemic by COVID-19. Risk measurement is carried out using the value at risk (VaR) and Median Shortfall (MS), applying a statistical methodology that considers the use of parametric and non-parametric resampling techniques (Bootstrapping). Data from five indices (Standard and Poor's 500, Dow Jones, COLCAP, VIX and Brent) were taken in order to evaluate the effects caused by variables such as the price of oil and the conditions generated by the COVID-19 pandemic on the dates of study, as the main result it is obtained that in general there is a very high volatility in the periods affected by the two aforementioned phenomena when they occurred simultaneously, and that in addition to large falls in the reference indices, there is also evidence of large recoveries that contribute positively to the trend in prices.
Keywords: G11; G15; G24; 330; Market risk; Volatility; Value at risk; Median Shortfall; Crisis; COVID-19; Financial markets